It Business Development Strategy of Zoom Infotek Telesindo Company in Public Sector Market With VTDF Business Model and VRIO Analysis - Musbakri, Musbakri; Asnawi, Yudha Heryawan; Asikin, Zenal (Jurnal Aplikasi Bisnis dan Manajemen, 2024)
Background: The Government Goods and Services Procurement Policy Agency (LKPP) plays a role in accelerating and simplifying the procurement process by implementing E-Catalog in accordance with Presidential Regulation Number 16/2018. The budget allocated by the government for electronic office equipment in 2021 is 50.1 trillion rupiah.Purpose: PT ZIT, which concentrates on hardware solutions, currently only reaches 0.086% of the huge market potential available. Implicating that PT ZIT needs to formulate a new strategy to achieve its target of 0.5% marketshare.Design/methodology/approach: In this research, PT ZIT used the Value Technology Distribution Finance (VTDF) method and Valueable, Rare, Inimitable, Organized (VRIO) Analysis.Findings/Result: The results show that PT ZIT has nine sustainable competitive advantages including the ability to retain labor, the ability to serve customers well, a large amount of portfolio, and has a good brand image and reputation in the IT business field. One of the main advantages is the ability to maintain a network with keyperson in the government which is valuable, rare, difficult to imitate, and organized. Conclusion: The study on PT ZIT's IT business model using the VTDF method and VRIO analysis identifies nine sustainable competitive advantages but highlights the need for further development. Advantages include a solid team, exceptional customer service, and a strong government network. The proposed strategy involves creating a public sector division, partnering with remote area businesses, collaborating with service centers and IT companies for after-sales service and HR, and improving the public sector consumer database to enhance competitiveness and market share.Originality/value (State of the art): This research significantly enhances understanding of IT business development in the public sector by uniquely combining the VTDF business model and VRIO analysis. It offers a comprehensive analysis of PT ZIT’s internal and external factors, providing a tailored strategy. Key findings emphasize strategic collaborations, specialized divisions, and improved customer relationship management. This study fills a literature gap on IT business strategies in the public sector, offering valuable insights and practical applications for other IT companies and future research. Keywords: IT business, public sector, strategic development, VRIO, VTDF